A capillary electrophoresis method to explore the self‐assembly of a novel polypeptide ligand with quantum dots. Issue 15 (11th July 2016) - Wang, Jianhao; Zhang, Chencheng; Liu, Li; Kalesh, Karunakaran A.; Qiu, Lin; Ding, Shumin; Fu, Minli; Gao, Li‐qian; Jiang, Pengju
Abstract : Polyhistidine peptides are effective ligands to coat quantum dots (QDs). It is known that both the number of histidine (His) residues repeats and their structural arrangements in a peptide ligand play important roles in the assembly of the peptide onto CdSe/ZnS QDs. However, due to steric hindrance, a peptide sequence with more than six His residue tandem repeats would hardly coordinate well with Zn 2+ in the QD shell to further enhance the binding affinity. To solve this problem, a His‐containing peptide ligand, ATTO 590‐E2 G (NH)6 (ATTO‐NH), was specifically designed and synthesized for assembly with QDs. With sequential injection of QDs and ATTO‐NH into the capillary electrophoresis with fluorescence detection, strong Förster resonance energy transfer phenomenon between the QDs and the ATTO 590 dye was observed, indicating efficient self‐assembly of the novel peptide onto the QDs to form ATTO‐NH capped QDs inside the capillary. The binding stability of the ligand onto the QD was then systematically investigated by titrating with imidazole, His, and a his‐tag containing competitive peptide. It is believed that this new in‐capillary assay significantly reduced the sample consumption and the analysis time. By functionalizing QDs with certain metal cation‐specific group fused peptide ligand, the QD‐based probes could be even extended to the online detection of metal cations for monitoring environment in the future.